Age‐related differences in the relations between individualised HRM and organisational performance: a large‐scale employer survey. (20th November 2014) - Bal, P. Matthijs; Dorenbosch, Luc
<x xml:space="preserve">Abstract</x> The current study aimed to investigate the relationship between individualised HRM practices and several measures of organisational performance, including the moderating role of employee age in these relationships. A large‐scale representative study among 4, 591 organisations in the Netherlands showed support for the relationships between individualised HR practices with organisational performance. Employee age moderated the relationships between the use of individualised practices and sickness absence and turnover, such that organisations with a high percentage of older workers benefited from work schedule practices, and organisations with high percentage of younger workers benefited from development practices.